Teaching brief motivational interviewing to medical students using a pedagogical framework. Issue 7 (July 2022) - Edwards, Elizabeth J.; Arora, Bharti; Green, Patricia; Bannatyne, Amy J.; Nielson, Tracy
Highlights: Brief motivational interviewing training was delivered using a pedagogical framework. Pre-clinical medical students received two lectures, and used a scaffold resource in role-plays and sessions. Confidence and knowledge increased from baseline to post teaching and remained at 3-months. Brief motivational interviewing skills improved across the practice sessions. Results support the Learn, See, Practice, Prove, Do, Maintain pedagogical framework and scaffolding. Abstract: Objective: Medical schools are charged with assisting medical students to acquire the confidence, knowledge and skills for behavior change conversations in primary healthcare. The present study evaluated teaching brief motivational interviewing (MI) to pre-clinical medical students. Methods: Forty-six students participated in an educational intervention premised on the Learn, See, Practice, Prove, Do, Maintain pedagogical framework, comprising 2 × 2-h lectures, a 2-h role-play triad session, and 3 × 2-h small group simulated patient encounters supported by scaffolding strategies. Measures of brief MI knowledge (MI Knowledge and Attitudes Test & Multiple-Choice Knowledge Test) and confidence (MI Confidence Scale) were taken at baseline, post-training, and 3-month follow-up, and skills (Behavior Change Counseling Index) were assessed at three intervals during simulated patient encounters. Results: Students who received brief MI training improved in knowledge and confidence from baseline to post-training and gains remained at 3-months. Brief MI skills improved across the simulation sessions. Conclusion: Pre-clinical medical students can attain knowledge, confidence and skills in brief MI after participation in a short intervention and improvements are sustainable. Practice implications: Our results support the use of an evidence-based pedagogical framework for teaching brief MI in pre-clinical years of medical curricula and our scaffolding strategy affords promise.